FATHER PARENTING ROLE IN THE CHILD’S SOCIAL-EMOTIONAL DEVELOPMENT - Onih Ratningsih; Reni Anggraeni Sadiah; Sri Nurhayati; Novi Widiastuti (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2021)
The role of fathers in parenting and child education will have a significant influence on child development. This study aims to describe the involvement of fathers in childcare and to know the picture of fathers' role in shaping the emotional social of the child. This study used a descriptive qualitative approach with the research subjects of 10 parents who had children aged 4-6 years and two teachers in Tk Selaras. Data collection techniques in the form of interviews, questionnaires, observations, and documentation studies. The results showed that the father's involvement in parenting could have a good influence on the child's personality so that he is ready to compete in the future. The quality of a meeting brings a more significant impact on the parenting carried out. The quality of good interaction between the child and the father can improve the child's emotional and social development because good interaction will make the child feel happy and have reasonable confidence.